Overview Of Criminology Of Criminal Actions Of Narcotics In Jayabakti Village - Ronaldi Timpola (Estudiante Law Journal, 2021)
The purpose of this study was to determine and analyze through a criminological review the factors that cause narcotics abuse by the people of Banggai Regency, especially in Jayabakti Village, and efforts to prevent narcotics abuse in Jayabakti Village. The type of research used is empirical or field research with a case approach (case approach). The results of this study indicate that narcotics abuse in Jayabakti village is caused by several factors, including the entry of outsiders (non-local communities), education, economy, and weak village security supervision. And prevention efforts are made so that the community is not involved in narcotics abuse, among others, Pre-Emtif efforts: Instilling moral values as the main fortress that can prevent not being influenced and falling into narcotics abuse and providing correct and intensive information to the public regarding the dangers of using drugs. Narcotics. Preventive efforts: Carry out communicative supervision and guidance to parents and families, the community environment, and the role of the local government to carry out information on the dangers of narcotics. Repressive measures: Law enforcement actions carried out by Banggai Police and BNN, rehabilitating perpetrators so that perpetrators have a strong desire to recover,in RUTAN, and providing skills training..